Neutrophil-to-lymphocyte ratio: association with microcirculatory changes detected by nailfold capillaroscopy in scleroderma patients and its relation to disease severity - Rasha M. Hammoda; Nermin H. El-Gharbawy; Ahmed A. Khalifa; Amira A. Moharram; Rahma A. Elziaty (Egyptian Rheumatology and Rehabilitation)
Abstract Background Microvascular alteration in scleroderma patients is well documented. Microcirculatory changes can be visualized by nailfold capillary microscopy (NFC) examination which is a safe and noninvasive technique. This study aims to identify possible association between neutrophil-to-lymphocyte ratio (NLR) and microvascular changes detected by nailfold capillaroscopic examination in scleroderma patients. Results The study was conducted on 25 patients with systemic sclerosis. On studying the correlation of NLR with laboratory parameters, we found significant positive correlations with erythrocyte sedimentation rate “ESR” and C-reactive protein “CRP” values (p = 0.000). Regarding the clinical manifestations, higher NLR was significantly related to the presence of digital ulcer (p = 0.023) and Raynaud’s phenomenon (p = 0.015). There was significantly negative relation between NLR with cyclophosphamide treatment. Regarding NFC examination’s results, there was significant negative correlation of NLR with capillary number/mm (p = 0.000) and significant positive correlation of NLR with capillary width (p = 0.005), and a significant relation of NLR with the presence of capillary hemorrhage and presence of active scleroderma pattern (p = 0.010) was also reported. Conclusion High N/L ratio as a marker of inflammation was found to reflect severity of systemic sclerosis and is associated with larger capillary diameter and lower capillary number in nailfold capillaroscopy. Active scleroderma pattern was associated with high N/L ratio. Further longitudinal studies are needed to determine the frequency of nailfold videocapillaroscopy and N/L ratio.